2021
DOI: 10.1111/jace.18257
|View full text |Cite
|
Sign up to set email alerts
|

A novel porous La2Zr2O7 ceramic aerogels with ultralow thermal conductivity and photocatalytic property

Abstract: Porous La 2 Zr 2 O 7 ceramic aerogels (CAs) were prepared by sol-gel template method and thermal treated process. The microstructure and crystallisation behavior of the samples were systematically characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), and Raman spectroscopy. The results indicated that the asprepared porous La 2 Zr 2 O 7 CAs had a single-phase pyrochlore structure with typical three-dimensional (3-D) porous structure. Meanwhile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Pan and co-workers observed that the defect-to-ordered phase structure in La 2 Zr 2 O 7 occurs at 875 °C when the material contains both fluorite and pyrochlore structures. The heterostructure formation is found to produce an increased surface area and varied grain boundaries that make it a budding choice for electrocatalytic applications. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan and co-workers observed that the defect-to-ordered phase structure in La 2 Zr 2 O 7 occurs at 875 °C when the material contains both fluorite and pyrochlore structures. The heterostructure formation is found to produce an increased surface area and varied grain boundaries that make it a budding choice for electrocatalytic applications. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The heterostructure formation is found to produce an increased surface area and varied grain boundaries that make it a budding choice for electrocatalytic applications. 14,45,46 In this study, we designed a novel heterostructure of 2D-MoS 2 nanoflakes assembled on a mixed phase of La 2 Zr 2 O 7 nanofibers (MoS 2 @LZO), which exhibits outstanding PEC-NRR activity. MoS 2 -coated La 2 Zr 2 O 7 heterostructures (MoS 2 @LZO) are synthesized via a facile hydrothermal technique at 220 °C for 24 h using Na 2 MoO 4 •2H 2 O as the Mo source and C 2 H 5 NS as the S source with calcined La 2 Zr 2 O 7 electrospun nanofibers (LZO) as a substrate/ template.…”
Section: Introductionmentioning
confidence: 99%